2019
DOI: 10.3390/nano9091213
|View full text |Cite
|
Sign up to set email alerts
|

Nanotechnology in Cement-Based Materials: A Review of Durability, Modeling, and Advanced Characterization

Abstract: In the context of increasing applications of various nanomaterials in construction, this work reviews the renewed knowledge of nanotechnology in cement-based materials, focusing on the relevant papers published over the last decade. The addition of nanomaterials in cement-based materials, associated with their dispersion in cement composites, is explored to evaluate their effects on the resistance of cement-based materials to physical deteriorations, chemical deteriorations, and rebar corrosion. This review al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
46
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(55 citation statements)
references
References 146 publications
(231 reference statements)
1
46
0
1
Order By: Relevance
“…With the advancement of nanotechnology, the mixing of nanomaterials into cement-based materials has been increasingly researched. A wide variety of nanomaterials have been investigated, including nano-silicon oxide [ 23 , 24 , 25 ], nano-titanium oxide [ 26 ], carbon nanotubes [ 27 , 28 , 29 ], sulfonated graphene [ 30 , 31 , 32 ], and graphene oxide (GO) [ 33 , 34 , 35 , 36 , 37 ]. GO is a new type of nanomaterial with excellent mechanical properties and good dispersion properties.…”
Section: Introductionmentioning
confidence: 99%
“…With the advancement of nanotechnology, the mixing of nanomaterials into cement-based materials has been increasingly researched. A wide variety of nanomaterials have been investigated, including nano-silicon oxide [ 23 , 24 , 25 ], nano-titanium oxide [ 26 ], carbon nanotubes [ 27 , 28 , 29 ], sulfonated graphene [ 30 , 31 , 32 ], and graphene oxide (GO) [ 33 , 34 , 35 , 36 , 37 ]. GO is a new type of nanomaterial with excellent mechanical properties and good dispersion properties.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, SP is added to cement paste for two reasons. Firstly, SP is added to improve the workability of the cement paste, since the w/c ratio was chosen to be small and the addition of nanomaterials will cause the workability of the cement paste to deteriorate [ 53 , 54 ]. Secondly, SP is used as a surfactant to disperse the nanomaterials in the cement matrix [ 53 ].…”
Section: Methodsmentioning
confidence: 99%
“…Firstly, SP is added to improve the workability of the cement paste, since the w/c ratio was chosen to be small and the addition of nanomaterials will cause the workability of the cement paste to deteriorate [ 53 , 54 ]. Secondly, SP is used as a surfactant to disperse the nanomaterials in the cement matrix [ 53 ]. Although these nanomaterials can be relatively stable dispersed in aqueous solutions after sonication, previous studies have shown that, in the alkaline environment of the cement matrix, the dispersion of CNTs and GO will be reduced, causing agglomeration [ 55 , 56 ].…”
Section: Methodsmentioning
confidence: 99%
“…Ordinary Portland cement (OPC), which acts as a glue in concrete, is the most widely used building material owing to its low cost and excellent performance 1 . It has been in use for more than 173 years, and currently, over 4 billion metric tons of OPC are used annually.…”
Section: Introductionmentioning
confidence: 99%